Synthesis and design of dual-wideband bandpass filters with internally-coupled microstrip lines - Zhang, Runqi (2014)
A class of dual-wideband bandpass filters (BPFs) with internally-coupled microstrip lines has been proposed and exactly synthesized in this paper. The generic structure of the proposed filters is formed by folding a multi-mode resonator (MMR) along its symmetrical plane and coupling a pair of short-circuited stubs on the two ends of the MMR. Thus, two coupling paths, one from the folded MMR and another from the coupled stubs, are used to generate additional transmission zeros (TZs) between the two passbands. A general synthesis procedure is developed for the synthesis of these BPFs by matching the transfer function of the circuit to the prescribed filtering function. As a design example, a 1st order BPF is firstly formed by using the coupled short-circuited stubs to illustrate the tunable distribution of the two reflection zeros. Secondly, a 2nd order dual-band BPF is designed with fully internally-coupled microstrip lines to provide an extra degree of freedom in determination of the design parameters. Next, a 3rd order BPF is partially coupled to have an explicit expression of the generated TZs. Finally, a 2nd-, 3rd-order and a cascaded case are synthesized and designed. The experimental results agree closely with the synthesized and designed ones.